Method for producing aluminum material for electrolytic capacitor electrodes and method for producing aluminum electrode material for electrolytic capacitors
By forming a recessed area on the surface of the aluminum substrate and controlling the etching conditions, the problem of controlling the starting point of the aluminum foil etching is solved, and the capacitance of the capacitor is improved.
Patent Information
- Application Number
- JP2021086122
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-05-21
AI Technical Summary
The prior art is difficult to accurately control the starting point of etching on the surface of aluminum foil, resulting in limited increase in etching area and inability to achieve the expected capacitance.
By forming a large number of recessed areas on the surface of the aluminum substrate as the starting point of etching, and controlling the temperature, humidity and time during the etching process, ensuring that the etching conditions are carried out within a specific range, inhibiting the growth of the inner layer of the oxide film, and ensuring the reliability of the starting point of etching.
The effective expansion of the surface area of the aluminum electrode material is achieved and the capacitance of the capacitor is improved.
Smart Images

Figure 0007628057000002 
Figure 0007628057000003 
Figure 0007628057000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an aluminum material for electrolytic capacitor electrodes and a method for producing an aluminum electrode material for electrolytic capacitors. [Background technology]
[0002] Aluminum foil, which is generally used as an electrode material for electrolytic capacitors, is subjected to electrochemical or chemical etching to increase the surface area of the aluminum foil in order to increase the capacitance. In order to increase the surface area, it is necessary to arrange the starting points from which etching starts at equal intervals and create more starting points for etching pits. For this purpose, a method of controlling the distribution of impurities contained in aluminum has been used. However, this method has limitations in controlling the impurity distribution, and it is impossible to precisely control the starting points of etching point by point. In other words, the conventional method has reached its limit in expanding the surface area by etching.
[0003] For this reason, a technology has been proposed in which depressions in a desired pattern are formed on the surface of an aluminum foil or on the surface of an aluminum foil having an oxide film by pressing a master mold having protrusions against the surface, and the starting point position is controlled by using these depressions as the starting points for etching, thereby producing an electrode foil with high surface area expansion efficiency (see Patent Document 1). In addition, a technology has been proposed in which a mold having protrusions is pressed against the surface of a smooth aluminum material for electrode foil having a surface roughness (arithmetic mean roughness: Ra) of less than 0.30 to form indentations in a desired pattern, such as recesses that break through the aluminum oxide film or protrusions by indentation transfer, and these are used as starting points for etching, thereby controlling the starting point position and producing an electrode foil with high surface expansion efficiency (see Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-74162 [Patent Document 2] JP 2007-042789 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the inventors' research has revealed that even if a large number of recesses that serve as the starting points of etching pits are formed, for example by pressing the aluminum substrate plane against a master mold, it may not be possible to obtain the expected capacitance.
[0006] As a result of further research into the cause of this, the inventors discovered that the occurrence and progression of etching pits are significantly affected by the temperature, humidity, and time of the atmosphere to which the aluminum material is exposed after a large number of recesses are formed on the surface of the aluminum base material and before it is subjected to etching.
[0007] The present invention has been made based on such findings, and has an object to provide a method for manufacturing an aluminum material for electrolytic capacitor electrodes, and a method for manufacturing an aluminum electrode material for electrolytic capacitors, which is an aluminum material having a large number of recesses formed in the aluminum base material that serve as starting points for etching pits, and which has excellent etching characteristics, can improve the surface expansion ratio, and can ultimately obtain a large electrostatic capacitance. [Means for solving the problem]
[0008] The above object can be achieved by the following means. (1) a step of pressing a master die having a number of protrusions against an aluminum base having an oxide film on a surface thereof to form a number of recesses on the surface of the aluminum base, the recesses being sites for forming etching pits; After the formation of the recesses, when the temperature (K) of the atmospheric air is a, the humidity (%) is b, and the time (hours) is c, a×c+a×b×c=d×10 4 Initiating etching under conditions where the value of d is 0 to 202; 1. A method for producing an aluminum material for electrolytic capacitor electrodes, comprising: (2) The method for producing an aluminum material for electrolytic capacitor electrodes according to the above item (1), wherein the value of d is 0 to 100. (3) A method for producing an aluminum electrode material for electrolytic capacitors, comprising subjecting an aluminum material produced by the method for producing an aluminum material for electrolytic capacitor electrodes according to the preceding item (1) or (2) to electrolytic etching or chemical etching. Effect of the Invention
[0009] The method for producing an aluminum material for electrolytic capacitor electrodes according to the present invention includes the steps of: pressing a matrix having a number of protrusions against an aluminum base having an oxide film on its surface to form a number of recesses on the surface of the aluminum base where etching pits are to be formed; and then, assuming that the temperature (K) of the atmospheric air is a, the humidity (%) is b, and the time (hours) is c, the formula: a×c+a×b×c=d×10 4 Since etching is started under the condition that the value of d in satisfies 0 to 202, the growth of the oxide film on the inner surface of the recess can be suppressed after the recess is formed and before etching starts. Therefore, during etching, the oxide film on the inner surface of the recess becomes the starting point of the etching pit, and etching pits are reliably formed at the positions of many recesses. As a result, it is possible to manufacture an aluminum material for electrolytic capacitor electrodes that can improve each area ratio and realize a large electrostatic capacitance.
[0010] According to the method for producing an aluminum electrode material for electrolytic capacitors according to the present invention, an electrode material for electrolytic capacitors having a large capacitance can be produced. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a cross-sectional view showing a state in which a large number of recesses are formed on the surface of an aluminum substrate. [Diagram 2] 1 is a cross-sectional view showing a state before a matrix for forming a large number of recesses is pressed against an aluminum base material. [Diagram 3] FIG. 11 is a cross-sectional view showing the state in which the mother die is pressed against the aluminum base material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] [Aluminum material for electrolytic capacitor electrodes] An aluminum material produced by the method for producing an aluminum material for electrolytic capacitor electrodes according to one embodiment of the present invention has a number of recesses, which are intended to be the locations for forming etching pits, formed on the surface by pressing a master die having a number of protrusions against an aluminum base material having an oxide film on its surface.
[0013] FIG. 1 shows a schematic cross-sectional view of an example of an aluminum material.
[0014] The aluminum material is composed of an aluminum base 1 having an oxide film 2 and a large number of recesses 3 formed on the surface thereof.
[0015] 1, each recess 3 has a pyramidal shape, and the shape of a cross section (hereinafter also referred to as a transverse section) of each recess 3 parallel to the plane of the aluminum base material may be any of a polygon, a circle, and an ellipse. The inner surfaces of these recesses 3 are entirely covered with an oxide film 4.
[0016] The surface of the oxide film 4 has many irregularities, voids, and cracks, and the average thickness of the oxide film 4 is thinner than that of the oxide film 2. The average thickness of the oxide film 2 is preferably in the range of 1 nm to 50 nm, and more preferably in the range of 2 nm to 20 nm. The average thickness of the oxide film 4 is preferably in the range of 0.5 nm to 40 nm, and more preferably in the range of 0.5 nm to 10 nm.
[0017] The maximum length of the opening of the recess 3 is preferably in the range of 0.01 μm to 10 μm, and more preferably in the range of 0.1 μm to 2.0 μm. In the example of Fig. 1, the recess 3 has a pyramidal shape, but the shape of the recess 3 may be any shape other than a pyramidal shape, such as a cylinder, a sphere, or an ellipsoid. The depth of the recess 3 is preferably in the range of 0.1 μm to 1.0 μm, and more preferably in the range of 0.2 μm to 0.6 μm.
[0018] The interval between the recesses 3 is preferably 1 μm to 10 μm. The interval between the recesses 3 refers to the minimum distance between the nearest recesses. If the interval between the recesses 3 is less than 1 μm, the etching pits formed in the recesses 3 during etching may communicate with each other, hindering the surface expansion effect of the etching pits. If the interval between the recesses 3 exceeds 10 μm, the number of etching pits may decrease, and it may not be possible to obtain a large surface expansion effect. The more preferable interval between the recesses 3 is 2 μm to 5 μm.
[0019] In the aluminum material for electrolytic capacitor electrodes manufactured by the manufacturing method according to this embodiment, the chemical composition of aluminum constituting the aluminum base 1 is not limited, and any material used as an electrolytic capacitor electrode material can be used as appropriate. Specifically, in order to regulate the amount of impurities and prevent deterioration of etching characteristics due to over-dissolution, the aluminum purity is preferably 99.9% or more, and particularly preferably 99.99% or more. The cube orientation occupancy rate of the aluminum material, or the occupancy rate of (100) is preferably 90% or more, more preferably 95% or more, and most preferably 99.9% or more. The thickness of the aluminum material for electrolytic capacitor electrodes is also not limited, and includes aluminum plates having a thickness of more than 200 μm, in addition to aluminum materials called foils having a thickness of 200 μm or less. The surface roughness (arithmetic mean roughness) of the aluminum base 1 is preferably less than 0.1 μm, and particularly preferably less than 0.05 μm. [Method of manufacturing aluminum material for electrolytic capacitor electrodes] The above-mentioned aluminum material for electrolytic capacitor electrodes can be produced, for example, by the following method.
[0020] An aluminum ingot having a predetermined chemical composition is subjected to a homogenization treatment, and then hot rolling, cold rolling, and final annealing are sequentially performed to form an oxide film, thereby producing an aluminum base material having an oxide film 2 on its surface. If the surface is smoothed by chemical polishing or electrolytic polishing after the final annealing, the aluminum base material is then exposed to the atmosphere to form a natural oxide film, thereby producing the aluminum base material. The oxide film 2 does not have to be a natural oxide film, and may be a chemical oxide film formed by chemical conversion treatment.
[0021] Next, a large number of recesses 3 are formed in the aluminum base 1. Although not limited to, a method for forming the recesses 3 may be, for example, a method in which a master die 100 having a large number of protrusions 101 as shown in Fig. 2 is pressed against the aluminum base 1 as shown in Fig. 3 to form the recesses 3 as indentations corresponding to the protrusions 101. By aligning the large number of protrusions 101 in the master die 100 to the arrangement of the recesses 3 described above, the recesses 3 can be formed in a desired pattern at desired positions on the aluminum base 1.
[0022] The master mold 100 may be produced by any method capable of producing a fine shape that can be subjected to the desired patterning, but is preferably produced by using mold processing or lithography technology. Any material may be used, regardless of whether it is electrically conductive or not, so long as it is harder than the aluminum base material 1. The shape of the protrusions 101 may be any of a cone, a column, a sphere, and an ellipsoid, and the outer shape of the protrusions becomes the inner shape of the recesses 3.
[0023] When pressing the matrix 100 against the aluminum base 1, the protrusions 101 and the aluminum base 1 are in contact perpendicularly. The pressing pressure must be increased according to the surface roughness of the aluminum base 1. In other words, if the aluminum base 1 is flat, uniform recesses 3 can be formed even with a low pressing pressure. The pressing method may be either a flat surface or a roll.
[0024] In the process of forming the recesses 3 by pressing the matrix 100 in the above-described manner, stress is applied to the inner surface of the recesses 3, causing irregularities, voids, cracks, and the like in the oxide film 4. If the matrix 100 is pressed deeper, the oxide film 4 becomes more easily stretched as the angle increases, resulting in a decrease in the average thickness.
[0025] The aluminum material thus formed with numerous recesses 3 is stored or transported in the atmosphere until it is used for etching. During storage or transport, the oxide film 4 on the surface of the recesses 3 is exposed to the atmosphere, causing oxygen and water to react with the aluminum, forming amorphous aluminum oxide and hydrated aluminum oxide. These are particularly likely to form in uneven, void, and cracked areas, which increases the average thickness of the oxide film 4. The oxide film 2 also increases in thickness, but since it is sufficiently thicker than the oxide film 4 due to being exposed to the atmosphere for a sufficiently long time before the recesses 3 are formed, its growth rate is much slower than that of the oxide film 4, and the growth of the oxide film 2 may be ignored. The inventors of the present application have discovered that the amount of growth of the oxide film 4 depends on the temperature, humidity, and exposure time in the atmosphere, and have found that these affect the surface expansion efficiency after etching and, in turn, the capacitance. The oxide film 4 grows through a process in which aluminum ions and oxygen ions diffuse through the oxide film. The amount of diffusion depends on temperature and time; the higher the temperature and the longer the time, the greater the amount of diffusion. The formation of aluminum oxide hydrate also depends on the amount of moisture. The greater the amount of moisture, i.e., the higher the humidity, the greater the amount of growth. In other words, the greater the atmospheric temperature, humidity, and exposure time, the greater the amount of growth of the oxide film 4, which does not become the starting point of etching pits and results in a loss of selectivity during etching.
[0026] Specifically, if the temperature (K) in the air is a, the humidity (%) is b, and the time (hours) is c, then a×c+a×b×c=d×10 4 The value of d in must be between 0 and 202. a×c+a×b×c=d×10 4If the value of d exceeds 202, the amount of growth of the oxide film 4 increases, and selectivity during etching is lost. It is particularly desirable for the value of d to be 0 to 100. Here, "in the atmosphere" refers to a state of 1 atmospheric pressure containing nitrogen, oxygen, argon, carbon dioxide, etc., which are components of air in the troposphere.
[0027] Furthermore, taking into consideration the operating environment of the etching equipment, from the press equipment for pressing the matrix 100 in an indoor environment, each numerical value is preferably within the following range. [1] a: 288~353K [2] c: 0.0008~ hour (3sec~) It is desirable that the temperature a be within the controllable temperature range of the etching solution. Also, considering the method of transporting the workpiece from the press equipment to the etching equipment, it is practically difficult to transport the workpiece within 3 seconds for the time c. When the temperature of the aluminum base 1 is lower than the temperature a of the atmosphere, moisture in the air condenses on the aluminum base, increasing the amount of growth of the oxide film, so it is desirable for the aluminum base 1 to always be at least the same temperature as the atmosphere.
[0028] The aluminum material for electrolytic capacitor electrodes thus produced is then etched to improve the surface area ratio. Pits are preferentially formed in the irregularities, voids, and cracks in the oxide film 4 on the inner surface of the recesses 3, because these have a high reactivity during etching. Therefore, the recesses 3 become the starting points for etching pits, and erosion progresses parallel or perpendicular to the (100) plane of the crystal grains to form tunnel pits. By generating etching pits in the desired recesses 3 that are regularly arranged, it is possible to reduce the reduction in effective area due to the combination of etching pits and the void regions of the pits. In other words, improving the pit generation rate in the desired recesses 3 leads to an improvement in the effective area. The pit occurrence rate for the recess 3 at the desired position can be determined at the time of formation of the initial pit before the formation of the tunnel pit. The initial pit here is a facet-type pit with a pit diameter and depth of 0.1 μm to 2 μm. The etching conditions are not limited, and may be electrochemical etching or chemical etching. As an example, the conditions for forming initial pits are shown below. Examples of the treatment liquid for electrochemical etching include an aqueous hydrochloric acid solution, or a solution in which sulfuric acid, nitric acid, or phosphoric acid has been added to an aqueous hydrochloric acid solution. The treatment liquid temperature is preferably 15°C to 80°C. In addition, a platinum electrode or a carbon electrode with an area sufficiently larger than that of the aluminum material is used as the counter electrode for the aluminum material, and the preferred current value is 100 mA / cm. 2 ~3000mA / cm 2 The preferred current application time is 0.01 s to 30.0 s. EXAMPLES
[0029] Examples of the present invention and comparative examples are shown below.
[0030] Recesses 3 were formed in an aluminum substrate 1 using a matrix 100 with projections, to produce an aluminum material for electrolytic capacitor electrodes.
[0031] The aluminum base 1 is an aluminum foil having a thickness of 120 μm and a composition of Si: 22 ppm, Fe: 16 ppm, Cu: 59 ppm, and Al purity of 99.99%, and has an oxide film 2 having a thickness of 0.003 μm formed on its surface. The arithmetic mean roughness Ra of the surface of the aluminum base 1 is 0.05.
[0032] The master mold 100 used was made of nickel and had numerous pyramidal protrusions 101 with a height of 1.8 μm formed on its surface at intervals of 2.1 μm. The numerous pyramidal protrusions 101 were arranged with the squares they constituted as unit lattices. Example 1 The matrix 100 was pressed against the aluminum base 1 with a surface pressure of 30 MPa in an atmospheric air atmosphere at a temperature of 293 K and a humidity of 40%, to form recesses 3 corresponding to the pyramidal protrusions 101 on the surface of the aluminum base 1 . Example 2 After Example 1, the aluminum base 1 was left to stand for 24 hours in an air atmosphere at a temperature of 293 K and a humidity of 0.8%, to obtain an aluminum material for electrolytic capacitor electrodes. Example 3 After Example 1, the aluminum base 1 was left to stand in an air atmosphere at a temperature of 293 K and a humidity of 40% for 72 hours to obtain an aluminum material for electrolytic capacitor electrodes. Example 4 After Example 1, the aluminum base 1 was allowed to stand in an air atmosphere at a temperature of 293 K and a humidity of 40% for 168 hours to obtain an aluminum material for electrolytic capacitor electrodes. Example 5 After Example 1, the aluminum base 1 was allowed to stand in an air atmosphere at a temperature of 293 K and a humidity of 5% for 960 hours to obtain an aluminum material for electrolytic capacitor electrodes. Example 6 After Example 1, the aluminum base 1 was left to stand in an air atmosphere at a temperature of 308 K and a humidity of 85% for 24 hours to obtain an aluminum material for electrolytic capacitor electrodes. Example 7 After Example 1, the aluminum base 1 was left to stand for 24 hours in an air atmosphere at a temperature of 333 K and a humidity of 85%, to obtain an aluminum material for electrolytic capacitor electrodes. Comparative Example 1 After Example 1, the aluminum base 1 was allowed to stand in an air atmosphere at a temperature of 308 and a humidity of 85% for 168 hours to obtain an aluminum material for electrolytic capacitor electrodes. Comparative Example 2 After Example 1, the aluminum base 1 was left to stand for 80 hours in an air atmosphere at a temperature of 333 K and a humidity of 85%, to obtain an aluminum material for electrolytic capacitor electrodes. Comparative Example 3 After Example 1, the aluminum base 1 was allowed to stand in an air atmosphere at a temperature of 293 K and a humidity of 40% for 960 hours to obtain an aluminum material for electrolytic capacitor electrodes. Comparative Example 4 After Example 1, the aluminum base 1 was allowed to stand in an air atmosphere at a temperature of 293 K and a humidity of 5% for 4800 hours to obtain an aluminum material for electrolytic capacitor electrodes. Comparative Example 5 After Example 1, the aluminum base 1 was allowed to stand in an air atmosphere at a temperature of 293 K and a humidity of 0.8% for 4800 hours to obtain an aluminum material for electrolytic capacitor electrodes. The 10 types of aluminum materials for electrolytic capacitor electrodes obtained above were immersed in a 6 mol / L hydrochloric acid solution at a temperature of 35°C and subjected to a current of 800 mA / cm 2 After electrolytic etching was performed at a current of 1000 Ω for 0.5 seconds, the sample was washed with pure water and dried.
[0033] The etched aluminum materials for electrolytic capacitor electrodes were observed by SEM to observe the occurrence of etching pits and to confirm the occurrence rate of pits for the recessed portion 3. The results were compared with those for each temperature, humidity, time, and a×c+a×b×c=d×10 4 The values of d in are shown in Table 1.
[0034] In Example 1, since etching was started immediately (actually 0.00083 hours later) after the recesses 3 were formed, d was set to zero.
[0035] [Table 1]
[0036] As shown in Table 1, in the aluminum materials for electrolytic capacitor electrodes according to Examples 1 to 7, the etching pits generated from the recesses 3 accounted for 75% or more of the total. For this reason, it was expected that a large surface expansion ratio and a high capacitance would be obtained.
[0037] In contrast, a×c+a×b×c=d×10 4 In Comparative Examples 1 to 5, in which the value of d is outside the range of the present invention, the etching pits generated from the recesses 3 were few, at 60% or less, and the surface expansion ratio was smaller than in the Examples, so that it was expected that the capacitance would be inferior. [Industrial Applicability]
[0038] The aluminum material produced by the method for producing an aluminum material for electrolytic capacitor electrodes of the present invention can be etched to obtain a high surface area expansion ratio, and when used as an electrode material, it is useful for improving the capacitance of an electrolytic capacitor. [Explanation of symbols]
[0039] 1. Aluminum substrate 2. Oxide film 3. Recess 4. Oxide film 100 Matrices 101 Protrusion
Claims
1. a step of pressing a master die having a large number of protrusions against an aluminum base having an oxide film on its surface, thereby forming a large number of recesses on the surface of the aluminum base, the recesses being sites for forming etching pits; After the recesses are formed, the temperature (K) of the atmospheric air is a, the humidity (%) is b, and the time (hours) is c, then a×c+a×b×c=d×10 4 Initiating etching under conditions where the value of d is 0 to 202; 1. A method for producing an aluminum material for electrolytic capacitor electrodes, comprising:
2. 2. The method for producing an aluminum material for electrolytic capacitor electrodes according to claim 1, wherein the value of d is 0 to 100.
3. 3. A method for producing an aluminum electrode material for electrolytic capacitors, comprising the steps of: subjecting an aluminum material produced by the method for producing an aluminum material for electrolytic capacitor electrodes according to claim 1 to electrolytic etching or chemical etching.
Citation Information
Patent Citations
Manufacture of aluminum foil for electrolytic capacitor electrode
JP1992036444A
Forming of electrolytic capacitor electrode foil
JP1999074162A
Method of manufacturing electrode foil for electrolytic capacitor
JP2007042789A
Anode, its manufacturing method, and solid electrolytic capacitor
JP2007214371A
Aluminum foil material for electrolytic capacitor anode, and method for producing the same
JP2009041100A